2017
DOI: 10.1097/sle.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleeve Gastrectomy on Thyroid Function in Chinese Euthyroid Obese Patients

Abstract: Weight loss after LSG is accompanied by significant decrease in serum TSH level but no change in serum FT4 and FT3 levels. However, further work is required to elucidate the mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…Several studies have found different results regarding the variation of TSH after weight loss surgery and the relationship between TSH variation and weight loss [15,16,17,18,19,20]. Most [16,17,19], but not all [15,20], studies evaluating the evolution of TSH after weight loss surgery have also found a decrease in circulating TSH after the intervention. In agreement with our results, Guan et al [16] performed a systematic review and meta-analysis of the effect of BS on thyroid function in obese patients and found that BS was associated with a significant decrease in circulating TSH levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found different results regarding the variation of TSH after weight loss surgery and the relationship between TSH variation and weight loss [15,16,17,18,19,20]. Most [16,17,19], but not all [15,20], studies evaluating the evolution of TSH after weight loss surgery have also found a decrease in circulating TSH after the intervention. In agreement with our results, Guan et al [16] performed a systematic review and meta-analysis of the effect of BS on thyroid function in obese patients and found that BS was associated with a significant decrease in circulating TSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of thyroid function and the effect of BS on postoperative thyroid function evolution are still not completely understood. There are several previous studies showing different results regarding the variation of thyroid-stimulating hormone (TSH) after BS and the relation of TSH variation with weight loss [15,16,17,18,19,20]. In addition, the mechanism and the clinical implications of this hormonal alteration remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that severely obese individuals may require higher L-T4suppressing or replacement therapy than normal weight subjects in association with impairment of the L-T4 pharmacokinetic parameters [8]. Decreased thyroid gene expression (particularly TSH-receptors) has been reported in visceral adipose tissue and subcutaneous in obese patients [9]. The decrease in adipose tissue in parallel with weight loss following obesity surgery results in corresponding changes in serum TSH and thyroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, thyroid hormones including free triiodothyronine, free thyroxine, and TSH declined in parallel at 12 months after RYGB and SG ( Yu et al, 2019 ; Zhu et al, 2019a ). However, weight loss after SG is accompanied by a significant decrease in serum TSH level, but no change in serum free thyroxine or free triiodothyronine levels ( Yang et al, 2017 ). Decreased TSH levels after weight loss induced by RYGB might be mediated by a decline in leptin ( Yu et al, 2019 ).…”
Section: Evaluation Of Metabolic Surgery Efficacy For Obesity and T2dmmentioning
confidence: 99%